Computing the durability of WAAM 18Ni 250 maraging steel specimens. Issue 12 (29th August 2022) - Peng, Daren; Jones, Rhys; Ang, Andrew S. M.; Michelson, Alex; Champagne, Victor; Birt, Aaron; Pinches, Samuel; Kundu, Sudip; Alankar, Alankar; Singh, Raman R. K.
Abstract: MIL‐STD 1530D requires that the certification of an aircraft part employ analytical tools that are capable of modeling crack growth. It is further stated that the durability and damage tolerance (DADT) analyses should be based on linear elastic fracture mechanics (LEFM) and follow a building block approach. This paper illustrates the durability analysis required to certify an additively manufactured part by using the examples of durability tests performed on two wire arc additively manufactured (WAAM) 18Ni 250 Maraging steel specimens. Highlights: Examines the growth cracks in WAAM 18Ni 250 maraging steel specimens with rough surfaces. Reveals that cracking in specimens with rough surfaces is characterized by a single equation. Illustrates the Hartman–Schijve equation for assessing specimens with rough surfaces.